Effect of various carbon and nitrogen sources on the biosynthesis of pectinliase enzymes in Penicillium cyclopium - Kaliyeva А.К.; Blieva, R.K.; Admanova, G.B.; Bakytzhankyzy, B.; Kemalova, N.K. (Fundamental and Experimental Biology, 2022)
This article studies the effect of carbon and nitrogen sources on the biosynthesis of pectinliase enzymes in Penicillium cyclopium. The carbon and nitrogen sources in the nutrient medium influence not only the constructive metabolism of P. cyclopium but also the synthesis of pectinliase enzymes. It is found that the best carbon source is fructose, which provides accumulation of polymethylgalacturonatliase (PMGL) and polygalacturonatliase (PGL) in culture fluid up to 5.0 and 5.7 units/ml. The best nitrogen source is ammonium chloride. When it was added to the nutrient medium as the only nitrogen source, the biosynthesis of pectinliase enzymes increased 2.8 times for polymethylgalacturonatliase (PMGL) and 3.0 times for polygalacturonatliase (PGL) compared with the control. The productivity of the culture increased to 9.2–11.4 units/g of mycelium. The optimal pH value for the growth and pectinliase enzymes biosynthesis was pH — 8.5. Determination of the activity of pectinliase enzymes and mycelium biomass in the culture fluid was carried out every 24 hours. The duration of the entire growing process lasted 168 hours. The most active enzyme biosynthesis takes place in the stationary phase for 3.0–3.5 days, followed by a sharp drop in activity after 4 days of cultivation. It is identified that the biosynthesis of pectinliase enzymes in P. cyclopium has a constitutive nature. Specific substrates did not induce the enzymes biosynthesis.